The Influence of Brand Image, Brand Trust, and Brand Love on Buying Attitudes of Teenage Girls - Syarach, Aliccia; Faerrosa, Lady; Dinna Widiyasti, Baiq; Amalia Wardi, Putri (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2025)
According to survey results, 54% of Indonesians prefer shopping online, with Gen Z being the most active group. Additionally, the majority of online shoppers by gender are female, accounting for 65%. The purpose of this study is to examine the influence of brand image, brand trust, and brand love on the attitude toward buying of teenage girls in Mataram City toward Colorbox products. This research employs a quantitative method, collecting data through questionnaires distributed to 150 participants. Using SPSS 24 for data processing, the study found that brand image has a positive but insignificant partial effect on attitude toward buying, brand love has a positive but insignificant effect on attitude toward buying, while brand trust has a positive and significant effect on attitude toward buying. However, when examined simultaneously, brand image, brand trust, and brand love have a positive and significant impact on attitude toward buying. This study highlights the significant role of brand trust in shaping the buying attitudes of teenage girls in Mataram toward Colorbox products. The findings offer valuable insights for marketers aiming to enhance brand strategies and consumer engagement in the rapidly growing online shopping market in Indonesia, particularly among female Gen Z consumers.